Edukasi Pencegahan Dampak Negatif Pinjaman Online Ilegal Terhadap Pelaku UMKM Kecamatan Pekalongan Timur, Kota Pekalongan - Bagus Ariyy; Muhammad Akbar Darmawan; Bagus Ariyandi; Rendy Septiyanto; M. Taufiq Abadi (CV.RIZANIA MEDIA PRATAMA, 2024)
Technological advances in the financial sector are growing rapidly. Technological innovation brings a more practical financial transaction process, one of which is applied to online loans. The implementation of Community Service activities (PkM) is motivated by the rampant illegal online loans offered to the public but not balanced with public knowledge of the online loans themselves. This has caused some MSME players to be trapped in online loan problems. The purpose of the PkM activity is to provide education to the community about digital finance which focuses on online lending material. The implementation of the PkM activity was carried out directly on May 22, 2023 at the culinary market of East Pekalongan District, Pekalongan City. The results of this PkM activity explain that understanding literacy around digital finance, especially on online loans, is very useful for MSME players. This can be seen from the results This service activity has increased participants' awareness of the importance of understanding the legality and risks of online loan fintech.